2014
DOI: 10.1002/hyp.10218
|View full text |Cite
|
Sign up to set email alerts
|

Tracing variability of run‐off generation in mountainous permafrost of semi‐arid north‐eastern Mongolia

Abstract: The headwaters of mountainous, discontinuous permafrost regions in north‐eastern Mongolia are important water resources for the semi‐arid country, but little is known about hydrological processes there. Run‐off generation on south‐facing slopes, which are devoid of permafrost, has so far been neglected and is totally unknown for areas that have been affected by recent forest fires. To fill this knowledge gap, the present study applied artificial tracers on a steppe‐vegetated south‐facing and on two north‐facin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…• the loss of shading and thick, insulating organic layers contribute to permafrost melt (Lange et al 2015), which in turn modifies infiltration pattern (for which permafrost acts as a natural barrier);…”
Section: Lessons Learned Preservation Of the Mountain Taiga Is A Prermentioning
confidence: 99%
“…• the loss of shading and thick, insulating organic layers contribute to permafrost melt (Lange et al 2015), which in turn modifies infiltration pattern (for which permafrost acts as a natural barrier);…”
Section: Lessons Learned Preservation Of the Mountain Taiga Is A Prermentioning
confidence: 99%
“…This is probably due to the loss of the organic layer modifying the moisture regimes, as well as the soil heterogeneity. Previous studies, which were conducted in summer 2012 on the same slope, found higher SWC and quick flow in the upper soil of SBF after intensive rainfall events, whereas lateral subsurface flow which recharges the Sugnugur river during dry season is common with relatively lower SWC in the upper soil of UBF [18,30]. The year-round mean liquid SWC, including unfrozen water, increases with depth at UBF site ( Figure S3, Supplementary Materials).…”
Section: Impact Of Wildfire On Active Layer Dynamicsmentioning
confidence: 71%
“…Precipitation patterns have changed, and these changes, in combination with drying trends of water bodies due to increasing temperatures and have resulted in loss of water bodies, including drying lakes and retreating glaciers (Unger-Sayesteh et al 2013;Kang et al 2015). Moreover, climate change and land reclamation for agriculture andin some regions-mining are important drivers of the degradation of both forests and riparian zones Kopp et al 2016;Lange et al 2015).…”
Section: Water Quality and Aquatic/riparian Ecologymentioning
confidence: 99%